Enhancing the processing efficiency, quality and storability of marinated eggs through ultrasonic/microwave combined technology - Huiqing Wu; Qi Zeng; Zhili Ma; Yongguo Jin; Yunzhong Chen (Food Chemistry: X, 2025)
This work applied ultrasonic marinating and microwave baking technology to enhance the sensory and storage quality of marinated eggs, addressing the low efficiency, poor quality, and short storability of conventional processing methods. The results indicated that ultrasonic marinating significantly improved salt permeation, enhancing the textural properties of egg white gel. After microwave baking, the water content of egg white gel reduced to 68.36 %, and water-holding capacity increased to 78.17 %. Notably, compared to the conventional method, the innovative technology boosted the processing efficiency by 6.98-fold and declined the water seepage rate by 56.37 % after 150 d storage. Besides, the combined technology increased the volatile flavor compounds of marinated eggs to 81 types. Correlation analysis revealed a significant correlation between T22 relaxation time and water-holding capacity (r = −0.88, p < 0.01). This work provided a theoretical foundation and practical solution for marinated egg processing and storage, showing potential for the egg product industry.